TEACHER PROFESSIONALISM IN THE COVID 19 PANDEMIC: A LITERATURE REVIEW - Irham Nugroho; Miftachul Huda; Suyadi Suyadi; Norma Dewi Shalikhah (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2022)
Covid-19 has caused a crisis of teacher professionalism degradation. It has surprised teachers at all levels and at the same time inspired them to seek solutions to problems they had never encountered before. Teachers and students are required to adapt to the new normal so that teachers transition in professional life from offline to online. This study aims to analyze the professionalism of teachers during the covid-19 pandemic, in terms of pedagogical, personality, social, and professional competencies. The method used is a systematic literature review (SLR), identifying, evaluating, and interpreting all findings on a research topic to answer pre-determined research questions using the preferred reporting item for systematic review and meta analytic (PRISMA). This research database uses Scholar, ERIC, and Mendeley. The results of the study show that teacher professionalism is decadent during the covid-19 period. pedagogical competence becomes highly cognitive because of the weak transfer of values online. personality competence has distorted the teacher's charisma because for almost two years the students have not met the teacher. Social competence of teachers fails to develop a sense of togetherness because of social and physical distancing. Besides that, the professionalism phase of teachers in Indonesia is in the collegial phase, pedagogic competence is considered more important than other competencies. In terms of personality competence, female teachers have a higher level of professional commitment than male teachers and the professional level of teachers with a master's degree education is significantly higher than the level of professional commitment of teachers with undergraduate education. Individual work professionalism is determined and monitored collectively. This means that the principal will be given decision-making authority over school policies and procedures and the support capacity of school leaders is needed. Pedagogy and professionalism during and after a pandemic will drive transformational change. Guidelines for professional behavior are needed to interpret what the professionalism of teachers looks like during the covid-19 pandemic. In conclusion, the concept of teacher professionalism is no longer relevant in the Covid-19 era. For future research recommendations, it is necessary to develop guidelines for professional teacher behavior during the pandemic, both COVID-19 and other natural phenomena that cause pandemics.